1996
DOI: 10.1183/09031936.96.09112313
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary herpes simplex in burns patients

Abstract: P Pu ul lm mo on na ar ry y h he er rp pe es s s si im mp pl le ex x i in n b bu ur rn ns s p pa at ti ie en nt ts s R.J. Byers*, P.S. Hasleton + , A. Quigley + , C. Dennett* ABSTRACT: In this study we aimed to determine the incidence of herpes simplex virus (HSV) in the lungs of burns patients, and its association with the presence of adult respiratory distress syndrome (ARDS) and pneumonia. Haematoxylin and eosin (H&E), and immunohistochemical (IHC) staining for HSV was performed on lung tissue from 54 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 28 publications
0
36
0
6
Order By: Relevance
“…HSV tracheobronchitis was first reported in 1949 [1]. Pulmonary involvement of the lower respiratory tract by HSV in adults has been reported in recipients of solid organ and stem cell transplantations [2,3], and in patients with burns [4], terminal cancer [5,6], AIDS [7] or patients receiving corticosteroids [8]. Herpes tracheobronchitis and bronchopneumonia have also been reported in immunocompetent patients, particularly in the elderly [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…HSV tracheobronchitis was first reported in 1949 [1]. Pulmonary involvement of the lower respiratory tract by HSV in adults has been reported in recipients of solid organ and stem cell transplantations [2,3], and in patients with burns [4], terminal cancer [5,6], AIDS [7] or patients receiving corticosteroids [8]. Herpes tracheobronchitis and bronchopneumonia have also been reported in immunocompetent patients, particularly in the elderly [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…HSV pneumonia should be suspected if patients also show mucocutaneous involvement. A high incidence of pulmonary HSV infection was described in the lungs of burn patients and especially associated with acute respiratory distress syndrome [18]. The diagnosis of HSV pneumonia usually requires tissue confirmation, and coinfection with other pathogens is not rare.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Additionally, Byers et al have demonstrated a strong association between HSV and adult respiratory distress syndrome (ARDS) in burn patients (6). In their study, 13 out of 16 ARDS cases were positive for HSV.…”
Section: Case Reportmentioning
confidence: 90%